Recycling of iron-rich sediment for surface modification of filters for underground water deironing. Issue 4 (August 2021) - Romanovski, Valentin; Romanovskaia, Elena; Moskovskikh, Dmitry; Kuskov, Kirill; Likhavitski, Vitaly; Arslan, Mehmet Faruk; Beloshapkin, Sergei; Matsukevich, Irina; Khort, Alexander
Abstract: Groundwater is one of the cleanest natural sources of drinking water available, which, at the same time, often requires deironing – removal of the dissolved iron ions – before the water could be used. In this paper, there are describe the preparation, characterization, and deironing properties of surface-modified refractory chamotte granules, used as active components of fillers for deironing filters. For this research, chamotte surface modification was made by solution combustion synthesis (SCS) approach of an aqueous solution of synthetic iron nitrate and citric acid with the different iron-to-chamotte ratios. An iron-rich precipitate from deironing filters was used as a source of iron for the preparation of a precursor solution. Obtained materials were characterized using diffraction, spectroscopic and microscopic methods. The SCS modification resulted in the formation of layers of hematite Fe3 O4 nanocrystallites of 5–15 nm on the surface of refractory chamotte granules. It was shown the effect of the dose of iron nitrate on the absorbed iron oxide species content on the surface of the modified chamotte granules and its influence on the surface and operational characteristics. Pilot-plant deironing tests showed that an increase in the concentration of iron on the chamotte granules surface from 5.8 wt% for unmodified samples, to 19.0, 48.7, and 55.8 wt% for the modified ones, led to the respective increase in the deironing efficiency from 41% to 65%, 73% and 78%, respectively. Graphical Abstract: ga1 Highlights: Solution combustion synthesis proposed for chamotte granules surface modification. Iron-containing sediments used as an efficient modifier of water deironing filters. Modification of chamotte increases the efficiency of water deironing on 45–78%. Surface modification does not affect the operational characteristics of filters.